The hormone replacement therapy (HRT) of menopause: focus on cardiovascular implications - Denti, Licia (Acta Biomedica Atenei Parmensis, 2010)
The hormone-replacement therapy for menopause has recently become matter of debate, especially after the first large randomized controlled trials failed to confirm the potential benefits on cardiovascular risk suggested by previous observational studies. On the contrary, the treatment has tuned out as to be potentially harmful, increasing the risk of stroke and of venous thromboembolism, without any benefit on coronary heart disease. Some factors, such as cardiovascular comorbidity, age and the time of treatment initiation since menopause, influence the clinical response to HRT, so that it can be considered relatively safe only in younger women, asymptomatic for cardiovascular disease and within 10 years from menopause. Evidences from studies on surrogate endpoints, including levels of the independent risk factors for atherosclerosis, suggest both beneficial and detrimental effects of female hormones on different steps of the process of plaque development, although with differences among different treatment regimens, depending on the type of estrogen and progestin employed, the dosage and the route of administration. Regimens including natural progestogens and using transdermal route, but, above all, Selective Estrogen Receptor Modulators (SERMs) such as raloxifene, are promising alternative to the oral estrogen-progestin treatment experimented in most trials, although no specific regimen can be considered completely safe. So, the updated guidelines on menopause management recommend a careful balance of risks and benefits for selection of women for therapy on an individual basis.